Is playing online games associated to students' emotional intelligence? - Fahsadilla, Syehan; Wibowo, Doddy Hendro (INSPIRA: Indonesian Journal of Psychological Research, 2024)
The emergence of emotional intelligence in students amidst the rampant trend of playing online games has both positive and negative impacts. This study examines the relationship between the level of involvement in online games and students' emotional intelligence. The research design is correlational, utilizing an accidental sampling technique with a total sample of 169 students from Salatiga. Data was collected using the Emotional Intelligence Scale and an instrument for online game playing intensity. The data analysis method employed was descriptive analysis using the instruments of online game-playing intensity and emotional intelligence as primary data in this study. The results indicate no significant relationship between online game-playing intensity and emotional intelligence. This suggests that the intensity of playing online games does not influence emotional intelligence.